A comparative study of practicing cross-infection control of dental prostheses and implant components among prosthodontists and dental technicians in Qassim province, Saudi Arabia - Sedky, Nabila Ahmed (International Journal of Infection Control, 2019)
The objectives were to compare the performance of infection control practices among prosthodontists and dental technicians in Al-Qassim Province, Kingdom of Saudi Arabia with regard to dental prostheses, impression copings, implant analogs and customized implant abutments (implant components). Self-administered questionnaires were submitted to 48 prosthodontists and 46 laboratory technicians in three cities. The questionnaires consisted of 19 questions for prosthodontists and 21 questions for laboratory technicians. All questionnaires were reviewed in situ to make sure they were fulfilled completely. A statistically significant difference was found between participants regarding receiving refresher infection control courses, while there was no statistical difference concerning disinfection protocols as well as communication regarding disinfection of prosthesis. For disinfection of different types of prosthesis before sending to lab/clinic, higher percentage of dentists applied this procedure (42.55% and 40.43%) compared to technicians (17.02% and 18.09%), while disinfection after return was higher among technicians (43.62% and 46.81%). Concerning implant components, dentists registered a low percentage for disinfection/sterilization of sent and returned items (13.83% and 7.45%), whereas 46.81% of technicians disinfect/sterilize implant components upon return from clinic.In conclusion, there was shortage of appropriate practice of infection control procedures in prosthodontic clinics and labs regarding the disinfection of dental prostheses as well as the disinfection/sterilization of implant components upon sent/returned to the dental lab/clinic.